PENERAPAN TOTAL PRODUCTIVE MAINTENANCE PADA DIVISI PRODUKSI (STUDI KASUS PT. XYZ BANDUNG) - Joshua Gianfranco; Muhammad Iqbal Taufik; Febri Hariadi; Muchammad Fauzi (Jurnal Taguchi : Jurnal Ilmiah Teknik dan Manajemen Industri, 2022)
Industry in each country has increased, as well as industry in Indonesia which is experiencing a fairly rapid increase. The improvement of product quality is that it can be done by carrying out maintenance to the machine used by the company. Total Productive Maintenance (TPM) is a process of machine maintenance carried out in industry to maximize and can increase productivity. PT XYZ is a manufacturing company that produces chemicals used for fabric production. This study aims to measure the level of effectiveness of the equipment used in PT. XYZ and measure how effective total equipment production. Determine the causal factors of low Overall Equipment Effectiveness (OEE) value and identify losses incurred, by providing proposed improvements in the factory by applying the TPM method. OEE values obtained in reactor engines at the plant in the period January-October 2021 with an average value reached of 55.63% - 60.60% are still below the overall equipment effectiveness (OEE) standard value caused by Quality Ratio which is still below jipm standard with an average value of 98.54%. Each company can find out the effectiveness of the machine used by using calculations of the level of effectiveness of equipment using the Total Productive Maintenance (TPM) method based on overall equipment effectiveness (OEE)values. Method is used to measure the number TPM by using the Overall equipment effectiveness (OEE) method. The use of this method to provide equipment performance results and accurate calculations to determine the effective engine that will be